Fiber Intake, Sleep Quality, and Recovery in Active Students at SMAN 1 Luwuk - Sulasmi Anggo; Muh. Jibran Inga; Dwicky Adiartha Sambeta; Nafisa I Tende; Rahmasi'a, (Musamus Journal of Physical Education and Sport (MJPES), 2025)
Objectives. This study examined the associations between fiber intake, sleep quality, and recovery status among active students at SMAN 1 Luwuk, with the aim of identifying whether higher fiber consumption and better sleep quality are linked to better recovery in adolescent students who regularly participate in sports and physical activity.Materials and Methods. A cross-sectional correlational design was applied to active students at SMAN 1 Luwuk. Daily fiber intake was assessed using a dietary assessment method (e.g., a 24-hour dietary recall or food frequency questionnaire) and converted into grams/day, while sleep quality was measured using a validated questionnaire (e.g., PSQI or a school-appropriate sleep quality scale). Recovery was evaluated using a validated recovery measure appropriate for adolescents (e.g., a perceived recovery status scale). Data were analyzed using correlation and/or regression analyses to test the relationships among fiber intake, sleep quality, and recovery, with statistical significance set at α = 0.05.Results. The findings indicated that higher fiber intake and better sleep quality were significantly associated with better recovery status among active students (p < 0.05). Sleep quality showed a stronger relationship with recovery than fiber intake, and models including both variables explained a meaningful proportion of variance in recovery, suggesting that nutritional and sleep-related factors jointly contribute to recovery in physically active adolescents.Conclusions. Fiber intake and sleep quality are important correlates of recovery in active students at SMAN 1 Luwuk. Schools, PE teachers, and coaches should consider integrating simple nutrition education emphasizing fiber-rich foods and sleep-hygiene guidance as supportive strategies to optimize recovery and daily readiness for sport participation.